ANALISIS PERAN AUDITOR DAN AKTUARIS DALAM PROSEDUR AUDIT ESTIMASI LIABILITAS IMBALAN KERJA - Eunike Nainggolan, Lois; Atmaja Wijaya, R. Muh.Syah Arief (Politeknik Negeri Jakarta, 2025)
This study aims to analyze the roles of auditors and actuaries in the audit process of employee benefits liability estimates, with an emphasis on cross-professional collaboration practices within Public Accounting Firms. The estimation of employee benefits liabilities involves a high degree of uncertainty and carries the risk of material misstatement, thereby requiring the contribution of actuaries as third-party experts with actuarial competence. Auditors are responsible for evaluating the reasonableness of the estimates prepared by actuaries while maintaining a professional level of skepticism. This research adopts a qualitative descriptive approach, utilizing interviews, direct observations, and document analysis conducted at Teramihardja, Pradhono, and Chandra Public Accounting Firm. The findings reveal that the relationship between auditors and actuaries is indirect and characterized by information asymmetry, whereby auditors continue to bear full responsibility for the audit opinion. The collaboration between the technical expertise of actuaries and the professional judgment of auditors is essential to ensure that the presented estimates are reasonable and comply with accounting standards, as reflected in the disclosures within the Notes to the Financial Statements.